2007
DOI: 10.1016/j.ces.2007.02.034
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of porous alumina-based catalyst coatings in microchannels

Abstract: Advances in the technology of micro-structured catalytic reactors depend crucially on the catalyst layer development. A detailed investigation on the influence of the different variables on the coating quality has lead to a procedure to coat commercial catalysts inside stainless steel microchannels with good adhesion and no loss of catalytic activity. A commercially available catalyst sample is directly slurry-coated inside the microchannels. These -structured catalysts are tested for the water-gas shift react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
63
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 10 publications
(13 reference statements)
2
63
0
Order By: Relevance
“…Other authors [9,10] performed similar studies replacing zinc with cerium. Furthermore, Germani et al [11] performed a systematic study on the nature of binders used for coating a Cu/Zn/Al catalyst into microchannels, and their influence on catalytic activity for the water gas shift (WGS) reaction. They concluded that binders play a major role on (i) slurry viscosity by their chemical structure but also through their molecular weight, (ii) coating adhesion and (iii) catalytic activity by redispersion of the active phase because of metal complexes formation.…”
Section: Introductionmentioning
confidence: 99%
“…Other authors [9,10] performed similar studies replacing zinc with cerium. Furthermore, Germani et al [11] performed a systematic study on the nature of binders used for coating a Cu/Zn/Al catalyst into microchannels, and their influence on catalytic activity for the water gas shift (WGS) reaction. They concluded that binders play a major role on (i) slurry viscosity by their chemical structure but also through their molecular weight, (ii) coating adhesion and (iii) catalytic activity by redispersion of the active phase because of metal complexes formation.…”
Section: Introductionmentioning
confidence: 99%
“…That low productivity of usually no more than 100 kg/m 3 h essentially reduced profitability of Fischer-Tropsch synthesis. One of methods of productivity improvement is based on change of physical and chemical properties of an internal surface of porous catalytic granules (see, for example [2][3][4][5][6]). In [7][8][9] it is supposed that limiting factor related to potential thermal instability of catalytic granules and reactor of synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Generally speaking, in the acid-free method organic molecules, more typically macromolecules, are used as dispersants. They are dissolved into the liquid phase so they can closely interact with the powder surface, allowing particle dispersion and slurry stabilization [27][28][29]. Many papers are reported in the literature regarding formulation and its effect on resulting slurries [30][31][32].…”
Section: Introductionmentioning
confidence: 99%